The rural price tag of California's clean energy transition - RANDLE, Sayd (Institutional Knowledge at Singapore Management University, 2022)
In the spring of 2019, residents of eastern California’s Owens Valley were on the fight. As is usual in that part of the world—where a century of aggressive water extraction by the Los Angeles Department of Water and Power has left the valley dry—they were angry about a water project dreamed up by some Southern Californians.